Bending the arc : striving for peace and justice in the age of endless war - Breyman, Steve; Amidon, John W., 1948-; Aumand, Maureen Baillargeon, 1946- (State University of New York, 2020)
"Since the late 1990s the annual Kateri Tekakwitha Interfaith Peace Conference in upstate New York has grown to become the region's premier peace conference. Bending the Arc provides a history of the conference and brings together the inspiring, personal stories from such well-known participants as Medea Benjamin, Blasé Bonpane, Kathy Kelly, Bill Quigley, David Swanson, and Ann Wright, among others. Drawing from diverse philosophical and spiritual traditions, contributors share their experiences of working for peace and justice and discuss the obstacles to both. They address a wide range of contemporary problems, including the war on terror, killer drones, the invasions and occupations of Afghanistan and Iraq, mass surveillance, the human cost of war, political-economic impediments to peace, violent extremism, the role of women in peace-building, and the continued threat of nuclear weapons. With its stories of how peace activists found their calling and its exploration of why the world still needs peace activism, the book offers a vision rooted in human community and hope for the future"--